Harnessing cerebral organoids for Alzheimer's disease research. (February 2022) - Bubnys, Adele; Tsai, Li-Huei
Abstract: Alzheimer's disease (AD) is a devastating neurodegenerative disorder affecting the aging population. Despite many studies, there remains an urgent need to identify the root causes of AD, together with potential treatments. Cerebral organoid technology has made it possible to model human neurophysiology and disease with increasing accuracy in patient-derived tissue cultures. Here, we review the most recent advances in modeling AD in organoids and other engineered three-dimensional cell culture systems. Early studies demonstrated that familial AD patient-derived organoids robustly develop disease pathology. Ongoing work has expanded this focus to investigate the genetic and environmental causes of late-onset sporadic AD and harness organoids for high-throughput drug screens. Future organoid models will need to incorporate additional cell types and tissues implicated in disease pathogenesis, including microglia and vasculature. We anticipate the continuation of this rapid progress in developing cerebral organoid technology toward facilitating our understanding of and informing treatment strategies for AD. Highlights: Cerebral organoids derived from patients with Alzheimer's develop disease pathology. Organoids model extracellular matrix dynamics underlying amyloid plaque formation. Organoids used to study role of APOE4 and other Alzheimer's risk genes. High-throughput drug screens with organoids are under development. Need to incorporate microglia and vasculature into organoids to improve relevance.